Cluster identification and analysis: Four regional cases in Spain - Jaime Del Castillo; Jonatan Paton (European Regional Science Association (ERSA), 2011)
The boom of clusters is leading to an 'explosion' of initiatives which in many cases lack an integrated approach. There are some methodologies which although strong technically, are expensive and often impossible to implement due to the shortage of basic information. This study proposes a methodology which combines both approaches using a set of defining and characterizing variables to identify and understand clusters at regional level. It has been tested in four Spanish regions with different economic profiles and a number of clusters, their impact and competitive levels have been analyzed. The methodology also proposes a dynamic analysis of clusters within the whole regional economic structure. This study examines the need for sound method of cluster analysis while providing an instrument not too restrictive in terms either the statistical information nor resource intensive.
Keywords: 330; clusters; mapping; impact; identification; dynamic analysis